Development of Mathematics Learning Media Based on Video Learning to Improve Distance Learning for Class VII Junior High School Students Material Numbers - Dwi jayanti, Anggraini (EduMatika: Jurnal MIPA, 2022)
The purposes of this development research is to determine the development of learning video media based on learning videos on the number material at SMPS Taman Siswa Medan. To improve the distance learning outcomes of junior high school students with numbers. The development model used in this development is the ADDIE model which has been modified from 5 stages to 4 stages, namely analysis (analysis), Design (design), Development (development) and implementation (implementation). The subjects of this study were made in small classes, namely students of SMPS Taman Medan students of class VII. The feasibility of this mathematics learning video refers to the results of the assessment of the learning video by media experts, material experts and math teachers. The mathematics learning video that has been developed gets a score by media experts with a score of 90 with the "very valid" eligibility category and the assessment of the learning video from a material expert with a score of 80 is categorized as "very valid" and finally the assessment from the math teacher with a score of 80 is categorized "very valid". Then the RPP assessment from media experts with an assessment of 90 with the "very valid" eligibility category. The assessment from material experts obtained a score of 80 with a "very valid" eligibility category and from a mathematics teacher with a score of 78 Categorized as "very valid". The results of the analysis of the effectiveness of students using distance learning videos obtained an average of 88.6 with an assessment category of "very good"